STUDENTS' ERROR IN SOLVING HOTS-CATEGORY MATHEMATICS PROBLEMS VIEWED FROM DIDACTIC TRIANGLE - Teddy Septian R; Suhendra Suhendra; Yaya Sukjaya Kusumah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Student errors in solving Higher-Order Thinking Skills (HOTS) category math problems can be caused by the learning process experienced by them. In the learning process, there are three interrelated components, namely students, teachers, and materials which can be described in a didactic triangle, namely Didactic Relationship, Pedagogical Relationship, and Didactic-Pedagogical Anticipation Relationship. This study aims to describe students' error in solving HOTS-category math problems and the causes of these errors viewed from the didactical triangle. This study used a case study method with a qualitative approach conducted at one of the senior high schools in Bengkulu Province, involving three 10th-grade students as research subjects. Data were collected by using test, interview, and document study techniques. The results of this research show that errors appeared in the completion of each HOTS-category math problem, consisting of errors in using concepts, calculations, and failing to solve the problem. Viewed from the didactic triangle, these errors occur when students do not learn through the resources provided, learning activities tend to be monotonous, passive-student responses during the learning process, and teacher only focuses on conventional learning. Thus, the learning process experienced by students is unable to encourage them to think at the HOTS level.